Patient preferences for treatments to delay bone metastases. Issue 15 (17th August 2014) - Hauber, A. Brett; Arellano, Jorge; Qian, Yi; González, Juan Marcos; Posner, Joshua D.; Mohamed, Ateesha F.; Gatta, Francesca; Tombal, Bertrand; Body, Jean‐Jacques
Abstract BACKGROUND Most patients with advanced prostate cancer (PCa) develop bone metastases (BM) and present with bone complications like fracture. Bone‐targeted agents that prevent metastasis‐induced bone complications can cause adverse events. Understanding how patients view treatment options may optimize care. This study aimed to quantify how PCa patients value a hypothetical treatment that delays BM but can cause osteonecrosis of the jaw (ONJ). The study also assessed the value patients place on avoiding metastasis‐induced bone complications versus increased survival. METHODS PCa patients from the United Kingdom (n = 201) and Sweden (n = 200) on androgen‐deprivation therapy or hormone therapy for ≥ 3 years completed a 10‐question discrete‐choice‐experiment survey examining whether patients would accept a BM‐delaying treatment. Two time‐tradeoff questions assessed patients' willingness to tradeoff between survival and bone complications. Percentages of patients choosing treatment were summarized by levels of treatment efficacy and ONJ risk. Odds ratios from a logit model were used to evaluate how patient and medication characteristics affected treatment choice. Proportions of patients choosing each tradeoff scenario were calculated. RESULTS A majority of patients accepted treatment at the lowest benefit level (5‐month BM delay) and highest risk level (9% ONJ risk). PCa symptoms and prior treatment affected patient preferences. Nearly 80% of patients would tradeoff at least 3 months of survival to avoid bone complications. CONCLUSIONS PCa patients in the UK and Sweden may value a medication that delays BM, despite the risk of ONJ. Furthermore, patients were willing to tradeoff up to 5 months of survival for prevention of bone complications. Prostate 74:1488–1497, 2014. © 2014 Wiley Periodicals, Inc.